Tinjauan Literatur Determinan Penyalahgunaan NAPZA pada Remaja berdasarkan Teori Health Belief Model Tahun 2013-2025 - Nayla Jasmine Fadillah; Luqman Effendi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Substance abuse involving Narcotics, Psychotropics, and Addictive Substances (NAPZA) among adolescents represents a significant and complex public health issue. According to data from the Indonesian National Narcotics Board (BNN) in 2023, the prevalence of NAPZA abuse reached 1.73% among individuals aged 15–64 years, with adolescents identified as a particularly vulnerable group. Adolescents’ susceptibility to substance abuse is influenced by various psychosocial factors, including family dysfunction, peer pressure, and emotional instability. This study aims to systematically review the determinants of NAPZA abuse among adolescents using the Health Belief Model (HBM) framework based on literature published between 2013 and 2025. A comprehensive literature review was conducted on 13 selected studies that met the inclusion criteria. The findings indicate that cues to action emerged as the most dominant HBM component influencing adolescent substance abuse behavior, followed by perceived susceptibility, perceived benefits, and perceived barriers related to ease of access to substances and unsupportive social environments. These results highlight the importance of integrating promotive and preventive interventions through family, school, and community-based education. Strengthening adolescents’ health beliefs through HBM-based interventions is expected to enhance risk awareness and foster sustainable preventive behaviors against substance abuse.